2019
DOI: 10.1055/s-0039-1695051
|View full text |Cite
|
Sign up to set email alerts
|

The Versatility of the Superficial Circumflex Iliac Artery Perforator Flap: A Single Surgeon's 16-Year Experience for Limb Reconstruction and a Systematic Review

Abstract: Background The superficial circumflex iliac artery perforator (SCIP) flap is a versatile option of free tissue transfer for small to large defects. In this study, we examine the advantages of the SCIP flap, its cadaveric anatomy, and clinical subtypes. Methods Ten cadavers were dissected and the corresponding pedicles of the SCIP and groin flaps were identified. A retrospective review of 20 clinical cases of free SCIP flap reconstruction was undertaken. The indication for reconstruction, flap dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…15,16 A recent cadaveric study came up to the same conclusion that the SCIP pedicle has a constant anatomy and it could be reliable. 17 A radioanatomical study from Gentileschi et al 18 have shown larger vessel diameters in superficial branches compared with deep branches of superficial circumflex iliac artery. 18 According to our analysis, SCIP flaps have a pedicle length and vessel diameter that could be adjusted to a wide range of recipient areas.…”
Section: Pedicle and Flap Characteristicsmentioning
confidence: 98%
“…15,16 A recent cadaveric study came up to the same conclusion that the SCIP pedicle has a constant anatomy and it could be reliable. 17 A radioanatomical study from Gentileschi et al 18 have shown larger vessel diameters in superficial branches compared with deep branches of superficial circumflex iliac artery. 18 According to our analysis, SCIP flaps have a pedicle length and vessel diameter that could be adjusted to a wide range of recipient areas.…”
Section: Pedicle and Flap Characteristicsmentioning
confidence: 98%
“…The mean diameter measured by CCDS (1.54 ± 0.38 mm) of the SCIP flap is comparable to that of the profunda artery perforator (PAP) flap (1.496 ± 0.39 mm), which was assessed by our research team in previous research [ 23 ]. Berner et al found the median diameter of the perforator and its concomitant vein was 1 mm (range 0.8–2 mm) [ 7 ]. Although contrary to its nomenclature, the SCIP flap may in reality be an axial flap with both the superficial or the deep branch of the SCIA giving off multiple small branches (perforators) to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Six flaps (2.9%) were lost despite revision [ 10 ]. Another series of 20 free SCIP flap transfers described a 100% flap survival [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10,12 The RFFF has continued to fall out of favor, as undesirable morbidity rates have been described. 2,3,25 Expanding upon its versatility, authors have detailed various flap thicknesses, such as the usage of the ultrathin flap, and myo-and osseocutaneous derivations, allowing for the resurfacing of a diverse catalog of defects, 9,14,26 and suggesting increased utilization where appropriately indicated. Our study serves to elucidate the attributes surrounding the SCIP flap and to contribute to the existing body of literature, regarding the efficacy of this flap.…”
Section: Discussionmentioning
confidence: 99%